Novus Orbis Sive America Meridionalis Et Septentrionalis Per Sua Regna, Provincias Et INsulas Iuxta Observationes Et Descriptiones Recentiss. - Seutter, Matthaeus, 1678-1756 (Homann Erben (Firm), 1730)
18th century Copper engraving handcolored with watercolor. Relief shown pictorially. Includes a compass rose in the Pacific Ocean. Printed in lower left corner in cartouche: "Novus Orbis Sive America Meridionalis Et Septentrionalis Per Sua Regna, Provincias Et INsulas Iuxta Observationes Et Descriptiones Recentiss. Divisa Et Adornata Cura Et Opera Matth. Seutter, Sac. Caes. Maj. Geogr. Aug. Vind." Printed in upper left corner in cartouche is a description of America's discovery and how Catholicism has spread: "Novus Orbis. Non ratione creations sed titulo inventions Anteriores insulae A 1492 a Christoph Columbo, Genuensi… Printed along bottom edge in lower right: "Cum Gratia et Privil. S. R. I. Vicartg, in partibg Reni, Sveviae, et Juris Franconici." Written in ink in upper right corner: "93." Written in pencil in upper right corner: "93." Depicts North and South America along with the West Indies, the Solomon Islands, the Azores, the Canary Islands, and part of West Africa and western Europe. South America has been divided into Terra Firma, Amozonum Regio, Terra Magellanica, Peru, Terra Firm, Brasilia, Chili, and Paraguay. North America includes Nova Mexico, Mexico as Hispania Nova, Florida, Louisiana, Virginia, New York, Pennsylvania, Terra Labrador, Greenland, Nova Britania, California and Terra Esonis Incogn. Of note, the far northwestern region of Canada marked as "Terra Esonis Incogn" is left blank and uncolored. California is shown here as an island with many place names along its west coast. The body of water between California and North America is labeled as Mare Vermeio Sive Mare Rubrum. The mythical kingdoms of Quivira and Anian are shown in the northwestern region of modern-day United States. Shows towns, rivers, mountains and forests pictorially. Contains some notes on geography and exploration. Throughout the Pacific Ocean are the routes, names and dates of various explorers including Ferdinand Magellan, Sarmien, Jacob le Maire, Alvaro de Mendaña de Neira, and Sir Francis Drake. Scenes of everyday life from the Americas adorn the cartouche in the lower left, while scenes of religious conversion accompany the two banners in the upper left with the inscriptions, "La Occident lux in Occidua orta" and, "Aeternas anhelat opes." On the left side of this cartouche are European explorers seated at a table with a banner above them containing the inscription, "Inventes facile est addere." Prime meridian: Teneriffe. Scale: 1:19,000,000. [West 170 degrees-East 20 degrees / North 80 degrees-South 50 degrees]. Georg Mathaus Seutter (1678-1756) was a map publisher and cartographer from Nuremberg who set up shop in Augsburg. After an apprenticeship with J. B. Homann in 1697, he began working in Augsburg and was eventually appointed Geographer to Imperial Court. Throughout his lifetime, he competed with his old mentor and worked closely with his son-in-law to put out a collection of town plans. His works include "Atlas Germanicus" (c. 1720), "Atlas Geographicus" (1725), "Atlas Novus" (1728), "Grosser Atlas" (c. 1735), "Atlas novus sive tabulae geographicae totius orbis" (c. 1741), and "Atlas Minor" (1744). After his death, his son, Albrecht Karl, continued the business (Moreland and Bannister, 87-8; Tooley, "Dictionary of Mapmakers," 557). This particular map was most likely first published in 1730 or 1731 though it was republished as late as 1784 (Wheat, 235, entry 199). Wheat describes this map as presenting "no new information" and even describes it as a "throwback" (148). The map largely follows the work of Sanson and Homann with a number of additions along the west coast of California including some rivers, two mountains and several place names including C de S Martin , I de S Augustin, C de la Trinite, P des Sarrdines, and C de Fortuna (Tooley, "California as an Island," No. 91, 132). There are a number of geographical inaccuracies including the large size of the Great Lakes and the vast width of South America (McLaughlin, 211). The illustrations surrounding the title cartouche of natives at work in the bottom left and the images of natives apparently practicing Christianity in the top left may symbolize the notion that natives without Christianity were "beneath" those who are enlightened by Christianity brought through Europeans (Louisiana State Museum). The concept of California as an island emerged roughly about the early seventeenth century. Many sixteenth-century maps, including work from Mercator, Ortelius and Wyfliet illustrate California correctly as a peninsula. Tooley attributes the island notion to a Carmelite Friar, Father Antonio Ascenscion, who probably formed the idea based on a "misconception" of reports from Juan de la Fuca in 1592 and Martin d'Aguilar in 1602. One of the explorers reported a large opening along the west and the other mentioned a large "inland sea" north of Cape Medocin. In 1620, Father Ascension sent a map of California as an island to Spain. The ship was caught by the Dutch. In 1622, a printed map from Herrera first showed California as an island. The idea really spread among English cartographers, however, with Briggs showing California as an island in 1625. Many Dutch cartographers ignored the idea and followed the work of their sixteenth-century predecessors. However, Visscher later promoted the idea as did Jannson in a 1638 map, further popularizing the geographic mistake. It was not until Father Eusebio Kino explored the area in the late seventeenth century that the island concept was completely confirmed as erroneous. Kino created a map that was published in 1705 showing California as a peninsula. Some cartographers resisted Kino's idea, such as Herman Moll who argued that some explorers had sailed around California. However, in 1746 another Spanish explorer confirmed that California was indeed a peninsula. In 1747, Ferdinand VI put out a royal decree that California was a peninsula (Tooley, "California as an Island," 110-11). Source(s): Louisiana State Museum. "Louisiana State Museum - Map Exhibit: So Much More Than Just a Map - Perspectives on Louisiana and the New World." Accessed 1 May 2009. <http://lsm.crt.state.la.us/6-1d.htm>. McLaughlin, Glen and Nancy H. Mayo. "The Mapping of California as an Island: An Illustrated Checklist." Saratoga, CA: California Map Society, 1995. Moreland, Carl and David Bannister. "Antique Maps: A Collector's Handbook." New York: Longman Group, Ltd., 1983. Tooley, Ronald Vere. "Chapter 3: California as an Island: A Geographic Misconception Illustrated by 100 Examples from 1625 to 1770." In "The Mapping of America." Ed. by Ronald Vere Tooley. London: Holland Press, 1985. 110-134. ---. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979. Wheat, Carl I. "Mapping the Transmississippi West." Volume 1. San Francisco: Institute of Historical Cartography, 1957.